2005
DOI: 10.1210/jc.2005-0330
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids and Retinol Differentially Regulate Steroid Biosynthesis in Ovarian Theca Cells Isolated from Normal Cycling Women and Women with Polycystic Ovary Syndrome

Abstract: Differential responses to retinol and retinoids in normal and PCOS theca suggest that altered retinoic acid synthesis and action may be involved in augmented CYP17 gene expression and androgen production in PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 42 publications
3
48
0
8
Order By: Relevance
“…For this reason, increased levels of atRA are also associated with arresting follicle growth [10]. In another study, it was reported that differential responses to retinol and retinoids in normal and PCOS theca suggest that altered retinoic acid synthesis and action may be involved in augmented CYP17 gene expression and androgen production in PCOS [11]. Therefore we investigated whether vitamin A (retinol) levels are related to PCOS.…”
Section: Discussionmentioning
confidence: 98%
“…For this reason, increased levels of atRA are also associated with arresting follicle growth [10]. In another study, it was reported that differential responses to retinol and retinoids in normal and PCOS theca suggest that altered retinoic acid synthesis and action may be involved in augmented CYP17 gene expression and androgen production in PCOS [11]. Therefore we investigated whether vitamin A (retinol) levels are related to PCOS.…”
Section: Discussionmentioning
confidence: 98%
“…It is also noteworthy that retinoids, which include retinol and its derivatives, have been found to regulate androgen biosynthesis and steroidogenic enzyme expression in normal and PCOS theca cells (Wood et al 2004). Wickenheisser et al further demonstrated that retinol stimulated CYP17 mRNA accumulation and promoter function in PCOS but not normal theca cells in humans, which could contribute to the excessive thecaderived androgen production in PCOS patients (Wickenheisser et al 2005). It would thus be intriguing to measure the hepatic level of RBP4 that transports retinol from the liver to target tissues.…”
Section: Retinol Binding Protein-4mentioning
confidence: 99%
“…Serum was assayed for hCGmediated ovarian theca cell steroid hormone release, including progesterone, and steroid hormones indicative of androgen biosynthetic enzyme activity (17α-hydroxyprogesterone (17αOHP), dehydroepiandrosterone (DHEA), androstenedione, and testosterone (44). Serum was also assayed for estradiol, at least partially reflecting ovarian granulosa cell aromatization of hCG-stimulated theca cell androgen release.…”
Section: Hcg Stimulation Testmentioning
confidence: 99%